Agricultural Economics 2021
DOI: 10.5772/intechopen.92702
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Efficiency of Vegetable Production in Nigeria: A Review

Abstract: Vegetables are important for maintenance of good health; their production and marketing are veritable sources of employment and livelihood. To promote vegetables' contribution to the above, there is a need for sustainable and efficient production process. The paper reviewed production, socioeconomic factors, and constraint affecting efficiency of production of three important vegetables (tomato, pepper, and onion). The review showed that socioeconomic factors found to increase technical efficiency in vegetable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…However, investigating the factors influencing efficiency in the adoption of climatesmart agriculture highlights strategies for improving productivity while mitigating climate risks. Technical efficiency refers to the ability of producers to obtain the maximum output from a given set of inputs, considering the current state of technology (Adeoye, 2021) [5] . In the case of maize production in Southeast Nigeria, technical efficiency measures how effectively farmers utilize resources such as land, labour, capital, and inputs like fertilizers and pesticides to maximize maize yields.…”
Section: Analytical Frameworkmentioning
confidence: 99%
“…However, investigating the factors influencing efficiency in the adoption of climatesmart agriculture highlights strategies for improving productivity while mitigating climate risks. Technical efficiency refers to the ability of producers to obtain the maximum output from a given set of inputs, considering the current state of technology (Adeoye, 2021) [5] . In the case of maize production in Southeast Nigeria, technical efficiency measures how effectively farmers utilize resources such as land, labour, capital, and inputs like fertilizers and pesticides to maximize maize yields.…”
Section: Analytical Frameworkmentioning
confidence: 99%
“…This can help them understand the need to examine and apply GAPs in agricultural activities. Educated farmers use improved practices to increase production (Ibitoye et al, 2015;Adeoye, 2020;Oyediran et al, 2020;Kabeer, 2003;Lapar and Ehui, 2003).…”
Section: Socio-demographic Characteristics Of Thementioning
confidence: 99%
“…"High number of household size could be due to the fact that vegetable producers in the study area practice polygamy and having large household size is a source of pride and a compelling force to produce more output by the household head in the farms " [21]. Adeoye [22]; Ajayi and Olutumise [23] reported that "production efficiency increases with increase in household size Formal education is a widely known avenue for improving knowledge and rate of skill acquisition". "Formal education is also important in agricultural business because it determines the degree of adoption of innovation and new technologies" [8,24].…”
Section: Socioeconomic Characteristics Of Vegetable Farmersmentioning
confidence: 99%